Entre o pranto e a mofa, a pátria idolatrada em Triste fim de Policarpo Quaresma, de Lima Barreto : sob a égide do arrivismo, a nação em seu rolar de Sísifo - Silva, Cinthia Mara Cecato da (2010)
The motto of this research is to show the (mis) direction that the Brazilian writer Afonso Henriques de Lima Barreto"s work traveled, giving new meaning to its importance in the literary sphere. Through an analysis that merges between the historical, social and fictional are exposed syntheses that will be about the settings of the Old Republic - the ground's history writer, the author of the aesthetic, beyond the projections on which its intellectual output was interpreted. In order to demystify its classification as an author of a minor literature, we sought to reveal how its production was modern, as it symbolized a break with the structure which oversees Academicist the time and the ideals focused on European parameters. Running along the nuances of national identity that confront Brazil's formal royal romance was elected Triste fim de Policarpo Quaresma in order to expose the prerogatives of the narrator's ironic tone transfigured the ills of the country ruled by an elite that seeks (ed) their own interests. In giving meaning to the novel in particular, intends to unveil the Brazilian enigma there imagined while configuring the fulcrum on which is founded the critical discourse of the writer transgressor.